Arahan Penyusunan dan Perancangan Masterplan Desa Wisata Madu Retno Berbasis Wisata Budaya - Ira Mentayani; Mohammad Ibnu Saud; Akbar Rahman; Irwan Yudha Hadinata (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2021)
Madu Retno Village is the first transmigration village in the Batulicin area which was formed in 1980. Initially, village management was under the guidance of the Transmigration Department with a duration of 1 year. The village is growing but not maximal in its stages. Judging from its potential, Madu Retno Village has a strong Hindu socio-cultural character. In its development, the existing potential has not been mapped thoroughly so that there is no complete planning and development scheme, it does not yet have the direction of goals contained in the development scheme, the thematic growth direction, and indicators to improve adequate infrastructure. The overall urgency can be realized through the preparation of a village master plan which will be prepared with the residents so that they will find and appreciate the expectations of the residents. The concept of an independent village is a top priority in the preparation of this village master plan, then the concept of a cultural tourism village becomes the next development effort so that Madu Retno Village will develop tourism and community culture independently.